THIN-LAYER DRYING KINETICS AND COLOR CHANGES OF POTATO SLICES DURING FAR-INFRARED VACUUM DRYING: THIN-LAYER DRYING KINETICS AND COLOR CHANGES OF POTATO SLICES DURING FAR-INFRARED VACUUM DRYING - Mitrevski, Vangelče (Journal on Processing and Energy in Agriculture, 2026)
In this study far infrared vacuum drying kinetics and change of color quality parameters of potato slices were analyzed. The      experimental data set of drying kinetics was obtained on the experimental set-up designed to imitate an industrial far infrared vacuum dryer. For approximation of the experimental data with regard to the moisture ratio (MR) three well known thin-layers drying models from scientific and engineering literature and model of Mitrevski et al., were used. The performed statistical analyzes show that the model of Mitrevski et al., has the best statistical performance than well-known thin-layer drying models. The estimated values of moisture diffusivity of potato slices obtained from this study are within the range from 5.14 × 10⁻⁸  to 5.01 × 10⁻⁹ m² s⁻¹. A negative effect on the total color change of far infrared vacuum dried potato slices was observed with increasing of temperature of infrared heaters and vacuum pressure.
Keywords: potato slices, thin-layer drying, color changes